2018
DOI: 10.3390/rs10122054
|View full text |Cite
|
Sign up to set email alerts
|

2D vs. 3D Change Detection Using Aerial Imagery to Support Crisis Management of Large-Scale Events

Abstract: Large-scale events represent a special challenge for crisis management. To ensure that participants can enjoy an event safely and carefree, it must be comprehensively prepared and attentively monitored. Remote sensing can provide valuable information to identify potential risks and take appropriate measures in order to prevent a disaster, or initiate emergency aid measures as quickly as possible in the event of an emergency. Especially, three-dimensional (3D) information that is derived using photogrammetry ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…In [109], the authors present an interesting approach to change detection that incorporates both 2D and 3D information. The 3D information refers to terrain information.…”
Section: Supervisedmentioning
confidence: 99%
“…In [109], the authors present an interesting approach to change detection that incorporates both 2D and 3D information. The 3D information refers to terrain information.…”
Section: Supervisedmentioning
confidence: 99%
“…Considering that vehicles are significantly higher than the ground, the available DSM can provide very useful height information to separate vehicles from background. The DSM we used has been generated with the same approach as described in [12]. In addition, spectral information and elevation information will be fused and encoded for the separation of objects and the ground, as well as the subsequent acquisition of object location information.…”
Section: Auto-tagging Label Generationmentioning
confidence: 99%
“…This dataset used in the paper is a subset from the aerial imagery of a camping site in northern Germany [12]. It was acquired by the optical 4K camera system on the German Aerospace Center (DLR) research helicopter BO 105 (DLR (CC-BY 3.0)) at a height of 600 m above the ground.…”
Section: Aerial Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…For 3D change detection, Qin et al [4] summarized the existing 3D change detection algorithms in detail. Gstaiger et al [13] concluded that using 3D change information combined with 2D information for change detection can deliver valuable indications. For the pixel-based method, Tian et al [14,15] used digital surface models (DSM) difference and threshold segmentation to detect building change.…”
Section: Introductionmentioning
confidence: 99%